The Role Of Islamic Leadership On Work Engagement In The Industrial Revolution 4.0: Work Ethic As Intervening Variable - Wijayati, Dewie Tri; Rahman, Zainur (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2022)
Islamic leadership is a universal leadership styles that are currently starting to be widely studied, because Islamic leadership does not only touch the worldly aspect, but also touches the spiritual aspect. The balance of these two aspects certainly affects the comfort of individuals in the organization by working optimism and enthusiasm so that it has a positive impact on organizational success. This study uses a quantitative approach by using surveys to collect the data. The sampling technique used purposive sampling, which the respondent’s criteria has a moslem leader, with a sample size of 146 respondents in the banking sector. The results showed that Islamic leadership has a positive effect on work engagement and work ethics. Then, work ethics has a significant positive effect on work engagement. Finally, work ethics mediates the influence of Islamic leadership on work engagement. Practically,  Islamic leadership gives a good environment to the employee by facilitated the work ethics to make employee dedicated and spirit in organization.